(untitled) (Annals of Medical Research, 2021)
Aim: Obstructive sleep apnea syndrome (OSAS) is characterized by transient obstruction of the upper airway and intermittent hypoxia during sleep and known to co-exist with a background low-grade systemic inflammation. In this study, we aimed to evaluate the routine hematological parameters which have recently been suggested as alternatives to specific inflammatory biomarkers and their association with disease severity and concurrent cardiovascular risk factors in OSAS. Material and Methods: 210 patients, who were examined for sleep disordered breathing complaints and diagnosed OSAS after overnight polysomnography, were included in the study. Patients who suffer from at least one of the following disorders; diabetes mellitus, hypertension and hyperlipidemia were classified as “patients with cardiovascular risk”. Results of routine hemogram studies and polysomnographic analyses were recorded.Results: 71% of the patients were male and 29% were female. 12% of the patients had mild, whereas 29% had moderate and 59% had severe obstructive sleep apnea syndrome. Platelet counts, mean platelet volume, platelet distribution width, neutrophil/lymphocyte ratio and platelet/lymphocyte ratio revealed no difference among three groups of disease severity. Comparison of patients with and without cardiovascular risk either showed no difference in terms of the aforementioned parameters.Conclusion: Our findings indicate that routine hematological parameters such as mean platelet volume, platelet distribution width, neutrophil/lymphocyte ratio and platelet/lymphocyte ratio are not appropriate indices for predicting disease severity and cardiovascular risk in OSAS patients. As severe disease corresponds to a worse inflammatory state, these markers might not be appropriate for predicting systemic inflammation either.